Effect of FAK inhibitor VS‐6063 (defactinib) on docetaxel efficacy in prostate cancer. Issue 4 (5th January 2018) - Lin, Hui‐Ming; Lee, Brian Y.; Castillo, Lesley; Spielman, Calan; Grogan, Judith; Yeung, Nicole K.; Kench, James G.; Stricker, Phillip D.; Haynes, Anne‐Maree; Centenera, Margaret M.; Butler, Lisa M.; Shreeve, S. Martin; et al.
Abstract : Background: Docetaxel, the standard chemotherapy for metastatic castration‐resistant prostate cancer (CRPC) also enhances the survival of patients with metastatic castration‐sensitive prostate cancer (CSPC) when combined with androgen‐deprivation therapy. Focal Adhesion Kinase (FAK) activation is a mediator of docetaxel resistance in prostate cancer cells. The aim of this study was to investigate the effect of the second generation FAK inhibitor VS‐6063 on docetaxel efficacy in pre‐clinical CRPC and CSPC models. Methods: Docetaxel‐resistant CRPC cells, mice with PC3 xenografts, and ex vivo cultures of patient‐derived primary prostate tumors were treated with VS‐6063 and/or docetaxel, or vehicle control. Cell counting, immunoblotting, and immunohistochemistry techniques were used to evaluate the treatment effects. Results: Docetaxel and VS‐6063 co‐treatment caused a greater decrease in the viability of docetaxel‐resistant CRPC cells, and a greater inhibition in PC3 xenograft growth compared to either monotherapy. FAK expression in human primary prostate cancer was positively associated with advanced tumor stage. Patient‐derived prostate tumor explants cultured with both docetaxel and VS‐6063 displayed a higher percentage of apoptosis in cancer cells, than monotherapy treatment. Conclusions: Our findings suggest that co‐administration of the FAK inhibitor, VS‐6063, with docetaxel represents a potential therapeutic strategy to overcome docetaxel resistance in prostate cancer.